Developing Islamic Tasks-Based Speaking English Materials for Islamic Elementary School Students: A Case Study at Elementary Schools in West Lombok, Indonesia - Bidari Andaru Widhi; Jupri Jupri; Jumadil Jumadil (Journal of Language and Literature Studies, 2023)
The present study aims to develop English Speaking Materials specifically designed for Islamic Elementary School students that adequately meet their language learning needs and preferences. In this regard, the study employs a Research and Development (R&D) ADDIE model, comprising five stages: analysis, design, development, implementation, and evaluation. The researcher not only acted as a materials developer but also as a teacher, since the data collection was conducted in the Islamic Elementary School. The participants in this study included 35 Islamic students and 2 Islamic teachers, and the data collection techniques utilized were questionnaires and structured interviews. The developed materials are grounded on a Project-based learning approach. The study investigates the need analysis for English Speaking Materials for Islamic Elementary School, describes the speaking materials for Islamic Elementary School, and evaluates their quality. The findings of the needs analysis reveal that elementary Islamic students aspire to enhance their fluency in English speaking and acquire more vocabulary to effectively communicate in formal and informal discussions. Accordingly, the developed materials consist of five units, equipped with tasks that incorporate inputs in the form of texts and videos, designed to facilitate the learning process. Moreover, the materials encourage creativity in exploring student knowledge. The study concludes by recommending that future researchers interested in this area utilize this study as an object of research and build upon its limitations. It is hoped that the outcomes of this research are of value to university students, who conduct research in the area of English Language Teaching.